Web Application for Measuring Learners' Knowledge of English Syntax: Analyzing the Relationship between Mouse Trajectories and Learners' Understanding. - Zushi, Mitsumasa; Miyazaki, Yoshinori; Norizuki, Ken (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities)
A major goal of this study is to provide a practical Web application for English word-reordering problems that records and reproduces learners' mouse trajectories. The authors believe that trajectories include useful clues to the nature of learners' processes for solving problems, including any hesitation they may experience in completing a task. In this paper, we will introduce the Web application we have developed so far and discuss ways in which to analyse the recorded mouse trajectories, such as the numbers of U-turns and drag and drops, in relation to the scores and newly incorporated 'degree of confidence' parameter. Empirical findings and statistical, correlation analysis from two experiments will support the conclusion that the mouse trajectories help to reflect learners' understanding more accurately than when their understanding is measured merely by their scores (that is, measured merely by their percentage of correct answers). It is our hope that the system will be applied as a tool for on-site teachers to develop their teaching strategies.